Evidence of Mycobacterium tuberculosis Complex bacteraemia in intradermal skin test positive cattle detected using phage-RPA - Swift, Benjamin; Convery, Thomas; Rees, Catherine (Taylor & Francis, 2016)
Bovine tuberculosis is a zoonotic infectious disease caused by Mycobacterium bovis 19 that affects cattle and can cause tuberculosis in a range of wildlife animals. A 20 bacteriophage-based method combined with PCR (phage-PCR) has been recently used to 21 detect and identify viable pathogenic mycobacteria in the peripheral blood mononuclear 22 cells (PBMCs) of animals suffering from paratuberculosis. To adapt this method for the 23 detection of M. bovis in blood, a new isothermal DNA amplification protocol using 24 Recombinase Polymerase Amplification (RPA) was developed and was found to be able to 25 detect M. bovis BCG within 48 h, with a limit of detection of approximately 10 cells per 26 ml of blood for artificially inoculated blood samples. When blood samples (2 ml) from a 27 Single Comparative Cervical Intradermal Tuberculin (SCCIT)- negative beef herd were 28 tested, Mycobacterium tuberculosis complex (MTC) cells were not detected from any 29 (45) of the blood samples. However when blood samples from SCCIT-positive animals 30 were tested, viable MTC bacteria were detected in 66 % (27/41) of samples. Of these 41 31 animals sampled, 32 % (13) had visible lesions. In the visible lesion (VL) group, 85 % 32 (11/13) had detectable levels of MTC whereas only 57 % (16/28) of animals which had 33 no visible lesions (NVL) were found to have detectable mycobacteraemia. These results 34 indicated that this simple, rapid method can be applied for the study of M. bovis 35 infections. The frequency with which viable mycobacteria were detected in the 36 peripheral blood of SCCIT-positive animals changes the paradigm of this disease.